ANALYSIS OF COHESION IN THE MAIN ARTICLES IN JAKARTA POST NEWSPAPER - WULANDARI, WULANDARI (2011)
The study is about describing the lexical and grammatical cohesions which are used in the main articles in Jakarta Post Newspaper. The objectives of this research are to describe the lexical cohesion and grammatical cohesion in the Main Articles in Jakarta Post Newspaper. This research is a descriptive qualitative study which analyzes the elements of cohesions of the main articles. The data are sentences which include the lexical and grammatical cohesions found in the Main Articles of Jakarta Post Newspaper. The writer collects the data by reading the articles, coding, making list on lexical and grammatical cohesion in the articles, and describing the lexical and grammatical cohesions toward Main Articles in Jakarta Post Newspaper based on Nunan‟s theory. The result shows that the cohesive devices in the Main Articles include the grammatical and lexical cohesions. The grammatical cohesions consists of refrence; (1)personal reference 41,57%, and demonstrative refrence 6,63%, (2)substitution 2,4%, (3)ellipsis 6,63% and (4)conjunction; Subordinative conjunction 15,67%, coordinative conjunction 9,64% and correlative conjunction 0,6%, while the lexical cohesions consists of (1)repetition 13,26%, (2)synonymy 2.4% and (3)hyponymy 1,2%. In the Articles, the use of grammatical cohesions are higher than the lexical cohesions. Keyword: grammatical cohesion, lexical cohesion and Main Articles in Jakarta Post Newspaper.